Varovanje in trajnostni razvoj kulturne pokrajine Ljubljanskega barja - Šmid Hribar, Mateja (Georitem, 2016)
The monograph ('Protection and sustainable development of a cultural landscape: the case of Ljubljana Moor') introduces research findings about the structure and functions of the Ljubljana Moor (Ljubljansko barje) cultural landscape. This landscape is composed of a plain with isolated hills (inselbergs) and hills on the outskirts. Floods are still frequent. Due to its exceptional biodiversity, in 2008 the area was proclaimed a landscape park. In the study we identified 28 landscape elements in 3 pilot sites - depending on the geological substratum, water, and land use - which contribute to landscape diversity. Payments to farmers have a significant impact on land use which influences greatly land cultivation and sustainable breeding, while these have a considerably lower influence on the preservation of semi natural landscape elements. We discovered that in terms of sustainability the key tendency is to strive to such a landscape diversity that ensures optimum landscape functioning and various ecosystem services.The analysis of landscape changes over 4 study periods showed that, initially, agriculture, settlement, and water management were the main drivers~however, over recent decades the importance of nature protection and tourism has increased. In today's landscape there are two conflicting trends: intensification and land abandonment .